Is renewable engery a suitable investment choice for South African non-bank institutional investors? - Molewa, Kholofelo (Research of GSB, 2017)
The research set out to examine the investment & economic suitability of Renewable Energy ("RE") assets for South African institutional investors. Data was collected through a series of structured and semi structured interviews and further triangulated and cross-checked through a thorough literature review of available policy documentation and academic literature. The limitations concerning this study have much to do with the nascent nature of the renewable energy program and therefore the lack of availability of hard economic and financial historical data. Further there is very little academic literature on renewable energy investing pertaining to a South African context. To mitigate some of the risks presented by the aforementioned limitations, interviewees were mainly subject-matter experts on the issue of RE investing and therefore provided key insights through a series of structured and semi-structured interviews. Within a South Africa specific context, there is very little academic material dealing with RE or infrastructure finance and investment. The implications of this study are therefore crucial in helping set the basis for the development of future theories around this and related topics. Interview discussions and review of other material revealed key themes, which allowed the researcher to discern some key findings: Firstly, there's a cautious but emerging consensus that the economic and financial features of RE assets make them suitable (and even attractive) for consideration in asset class allocation decisions. Further and related: the merging view was that RE assets could offer the benefit of both reducing risk and increasing expected returns within a given portfolio. A key related sub-theme and finding was the need to establish a common set of nomenclature, which would describe and ultimately help benchmark the economic and financial features of RE assets – the ability to benchmark financial and economic data being a key aspect of the asset allocation framework. Secondly data collected indicated that there is strong institutional support for government's energy policy and how it has been implemented to date. Thirdly, in working out the suitability of RE assets investors tend to default to comparable proxies such as bonds, equities, REITS. The emerging theme coming out of the data is that RE assets are likely to resemble fixed income assets in their financial and economic characteristics. Lastly, for all the emerging consensus in support of the government's RE policy, many investors seem to hedge their optimism and remain generally unsure and in some instances sceptical of the overall sustainability of the program, citing the fact that there are still too many unknowns regarding RE assets and their respective futures. This research therefore has some useful practical applications for institutional investors, hopefully further demystifying a sector that could be a lynchpin of the South African economy for some time to come.